(untitled) (Research, Society and Development, 2020)
This article presents quick reflections on the possibility of an integration between education and leisure as complementary sciences, in order to provide a better use of the studies and reflections proposed by some leisure scholars as an instrument of building citizenship. Aiming at teachers a possibility of reflection around the theme trying to think about possibilities of application in their daily classroom activity, without, however, presenting prescriptions. Unlike ordinary people, leisure goes far beyond a simple, but necessary moment of rest, leisure can and should be appreciated as an important educational vehicle, which fully meets the proposals presented by Brazilian legislation. To this end, this study was constructed methodologically in a qualitative way in a context of Action Research in its first part and a bibliographic research in its second part.